Electrophoretic characterization of cationic proteins and peptides of buffalo granulocytes - Sarmah, S; More, T (The Indian Journal of Animal Sciences, 2012)
Polymorphonuclear granulocytes contained both nonoxidant and oxidant microbicidal systems of which former is least characterized more particularly in buffaloes. Accordingly cationic proteins were extracted from buffalo peripheral granulocytes and mainly electrophoretically characterized by using AU PAGE. Out of total bands, 3 bands with Rm of 0.64, 0.71 and 0.83 were for peptides just preceding the lysozyme. The band with Rm of 0.87 corresponded with reference lysozyme, that is maximum cationicity. The remaining bands with relatively poor cationicity represented myeloperoxidase, lactoferrin, and elastase. The peptides on subjecting to the heating treatment lost their distinctiveness in AUPAGE. There was no appreciable effect of obtaining granules at 14, 18, 22 and 27 x 1000 g on AUPAGE pattern of their proteins. This was also not much affected by the age of animals. The peptides on treating with trypsin lost their band pattern and implied the presence of either arginine or lysine in the peptides. The glycoprotein staining of AUPAGE of acid extracted granular proteins revealed the presence of only 2 bands of glycoprotein type. The peptides isolated by preparative AUPAGE also contained no free-SH; carbohydrate groups and proteinase inhibitor activity.